Anode active material layer, battery, and method for manufacturing anode active material layer

JP2025029738AActive Publication Date: 2025-03-07TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023134527
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-07
Estimated Expiration
2043-08-22

AI Technical Summary

Benefits of technology

【0009】 本開示の負極活物質層によると、電池の放電容量及び抵抗を改良することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029738000001
    Figure 2025029738000001
Patent Text Reader

Abstract

To provide an anode active material layer capable of improving the discharge capacity and resistance of a battery, and a method for manufacturing the anode active material layer.SOLUTION: An anode active material layer for a battery includes a carbon-based anode active material and a binder that covers the carbon-based anode active material. The content of the binder is 4.0 to 9.0 mass% with respect to the total amount of the anode active material layer, and the coverage of the anode active material by the binder is 8.0 to 25%. A method for manufacturing an anode active material layer includes mixing a carbon-based anode active material and a binder of 4.0 to 9.0 mass% with respect to the total amount of the anode active material layer to prepare a negative electrode mixture, and coating the anode mixture onto a substrate by a dry process to form the anode active material layer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a negative electrode active material layer, a battery, and a method for producing a negative electrode active material layer. [Background technology]

[0002] A lithium ion secondary battery typically includes an electrode active material layer containing an electrode active material on a current collector. By forming this electrode active material layer homogeneously, the performance of a battery using this electrode active material layer can be stabilized. This electrode active material layer is generally manufactured by supplying a slurry-like electrode material, in which the electrode active material is dispersed in a liquid medium, to a current collector, drying it, and then consolidating it. On the other hand, the following manufacturing method (dry method) for manufacturing an electrode active material layer is also known, which does not use a liquid medium and omits the drying step, thereby saving energy and producing the layer at low cost.

[0003] For example, Patent Document 1 discloses a method for manufacturing an electrode, which includes (a) preparing granules containing an active material powder and a binder, (b) supplying the granules to a surface of a roll, (c) charging the granules, (d) transporting the granules from a first region to a second region by rotating the roll, (e) forming a first electric field between the second region and a third region to fly the granules from the second region to the third region, and (f) forming a second electric field between the third region and a substrate to fly the granules from the third region to the substrate, wherein the second region is lower than the first region in a vertical direction, the third region is separated from the second region in a direction intersecting the vertical direction, the substrate is lower than the third region in the vertical direction, and the granules adhere to the substrate to form an active material layer. According to the electrode manufacturing method of Patent Document 1, it is said that unevenness in coating can be reduced. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2023-016208 A Summary of the Invention [Problem to be solved by the invention]

[0005] The dry process can produce an electrode active material layer with reduced energy consumption and low cost by omitting the drying step, but there is still room for improvement in terms of discharge capacity and resistance of a battery including an electrode active material layer produced by the dry process.

[0006] Therefore, an object of the present disclosure is to provide a negative electrode active material layer that can improve the discharge capacity and resistance of a battery. [Means for solving the problem]

[0007] The present disclosure achieves the above object by the following means.

[0008] <Aspect 1> A negative electrode active material layer for a battery, the negative electrode active material layer includes a carbon-based negative electrode active material and a binder coating the carbon-based negative electrode active material, The content of the binder is 4.0 to 9.0% by mass with respect to the total amount of the negative electrode active material layer, and The coverage of the negative electrode active material by the binder is 8.0 to 25%. A negative electrode active material layer for a battery. Aspect 2: The negative electrode active material layer according to aspect 1, wherein the content of the binder is 6.0 to 9.0% by mass with respect to the total amount of the negative electrode active material layer. Aspect 3: The negative electrode active material layer according to aspect 1, wherein the content of the binder is 7.0 to 8.0% by mass with respect to the total amount of the negative electrode active material layer. Aspect 4: The negative electrode active material layer according to any one of Aspects 1 to 3, wherein the binder is polyvinylidene fluoride. A battery having the negative electrode active material layer according to any one of Aspects 1 to 4. A method for producing a negative electrode active material layer according to any one of Aspects 1 to 4, comprising the steps of: Mixing a carbon-based negative electrode active material and a binder in an amount of 4.0 to 9.0 mass% based on the total amount of the negative electrode active material layer to prepare a negative electrode mixture; and applying the negative electrode mixture onto a substrate by a dry process to form the negative electrode active material layer; The method for producing a negative electrode active material layer includes the steps of: <Aspect 7> A manufacturing method described in aspect 6, wherein the dry process is electrostatic painting. <Aspect 8> The carbon-based negative electrode active material has an average particle size of 5 to 30 μm, and The average particle size of the binder is 100 nm to 500 nm. The method according to embodiment 6 or 7. Effect of the Invention

[0009] The negative electrode active material layer of the present disclosure can improve the discharge capacity and resistance of the battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the gist of the present disclosure.

[0011] In the present disclosure, a "composite" refers to a composition that can constitute an anode (cathode) active material layer as it is or by further containing other components. Also, in the present disclosure, a "composite slurry" refers to a slurry that contains a dispersion medium in addition to a "composite" and can be applied and dried to form an anode (cathode) active material layer.

[0012] 《Negative electrode active material layer》 The negative electrode active material layer for a battery according to the present disclosure comprises: the negative electrode active material layer includes a carbon-based negative electrode active material and a binder coating the carbon-based negative electrode active material, The content of the binder is 4.0 to 9.0% by mass with respect to the total amount of the negative electrode active material layer, and The coverage of the negative electrode active material with the binder is 8.0 to 25%.

[0013] The negative electrode active material layer of the present disclosure can improve the discharge capacity and resistance of the battery.

[0014] The negative electrode active material layer for a battery according to the present disclosure includes a carbon-based negative electrode active material and a binder that covers the carbon-based negative electrode active material. The present inventors have conducted research and found that when the amount of the binder and the coverage of the negative electrode active material by the binder are within specific ranges, the discharge capacity and resistance of the battery are improved.

[0015] Although the details of the mechanism by which the discharge capacity and resistance of the battery are improved are not clear, it is assumed that the mechanism is as follows. It is generally known that a film (Solid Electrolyte Interphase (hereinafter referred to as SEI)) is formed on the surface of the negative electrode active material during charging and discharging of the battery. It is considered that by setting the binder amount in the negative electrode active material layer to 4% or more, the surface of the negative electrode active material is partially covered with the binder by the binder, suppressing the formation of SEI, and thereby suppressing the increase in irreversible capacity. On the other hand, it is considered that by setting the binder amount to 9% or less and setting the coverage rate of the negative electrode active material by the binder to 8.0 to 25%, the surface of the negative electrode active material is prevented from being excessively covered with the binder, suppressing the increase in contact resistance between the negative electrode active materials.

[0016] <Configuration of negative electrode active material layer> The negative electrode active material layer includes a carbon-based negative electrode active material and a binder that coats the carbon-based negative electrode active material.

[0017] The negative electrode active material layer may optionally contain a conductive assistant, a solid electrolyte, and the like.

[0018] (Carbon-based negative electrode active material) The carbon-based negative electrode active material is not particularly limited, and may be a carbon material capable of absorbing and releasing metal ions such as lithium ions. The carbon material is not particularly limited, and examples thereof include hard carbon, soft carbon, and graphite.

[0019] The average particle size of the carbon-based negative electrode active material is not particularly limited, but is preferably 5 to 30 μm from the viewpoint of obtaining a negative electrode active material layer with high discharge capacity and low resistance. The average particle size of the carbon-based negative electrode active material may be 5 μm or more, 7 μm or more, 9 μm or more, 11 μm or more, 13 μm or more, or 15 μm or more, and may be 30 μm or less, 28 μm or less, 26 μm or less, 24 μm or less, 22 μm or less, or 20 μm or less. Here, the average particle size can be determined by observation with a scanning electron microscope (SEM).

[0020] (Binder) The binder is not particularly limited. For example, the binder may be, but is not limited to, polyvinylidene fluoride (PVdF), butadiene rubber (BR), polytetrafluoroethylene (PTFE), styrene butadiene rubber (SBR), or a combination thereof. The binder is not particularly limited, but in terms of redox resistance and binding properties, polyvinylidene fluoride and polytetrafluoroethylene are preferred, and polyvinylidene fluoride is more preferred.

[0021] The average particle size of the binder is not particularly limited, but may be 100 nm to 500 nm. The average particle size of the binder may be 100 nm or more, 120 nm or more, or 140 nm or more, and may be 500 nm or less, 450 nm or less, 400 nm or less, 350 nm or less, 300 nm or less, or 250 nm or less. Here, the average particle size can be determined by observation with a scanning electron microscope (SEM).

[0022] (Conductive assistant) The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.

[0023] (solid electrolyte) The material of the solid electrolyte is not particularly limited, and for example, the solid electrolyte may be a sulfide solid electrolyte, an oxide solid electrolyte, a polymer electrolyte, or the like, but is not limited thereto.

[0024] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.

[0025] An example of an oxide solid electrolyte is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.

[0026] The sulfide solid electrolyte and the oxide solid electrolyte may be glass or crystallized glass (glass ceramic).

[0027] Examples of the polymer electrolyte include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.

[0028] (Negative electrode current collector layer) The negative electrode active material layer may be formed on the negative electrode current collector layer. The material used for the negative electrode current collector layer is not particularly limited, but any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, it may be copper, copper alloy, stainless steel (SUS), nickel, or these metals plated, coated, or vapor-deposited with nickel, chromium, carbon, etc., but is not limited thereto.

[0029] <Binder Content in Negative Electrode Active Material Layer> The content of the binder in the negative electrode active material layer is 4.0 to 9.0 mass % with respect to the total amount of the negative electrode active material layer.

[0030] The content of the binder in the negative electrode active material layer is not particularly limited, but from the viewpoint of improving the discharge capacity and resistance, it is preferably 6.0 to 9.0 mass % and more preferably 7.0 to 8.0 mass % relative to the total amount of the negative electrode active material layer.

[0031] The content of the binder in the negative electrode active material layer may be 4.0% by mass or more, 4.5% by mass or more, 5.0% by mass or more, 5.5% by mass or more, 6.0% by mass or more, 6.5% by mass or more, or 7.0% by mass or more, and may be 9.0% by mass or less, 8.5% by mass or less, or 8.0% by mass or less.

[0032] <Coverage rate of negative electrode active material by binder> The coverage of the negative electrode active material with the binder is 8.0 to 25%.

[0033] From the viewpoint of improving the discharge capacity and resistance, the coverage of the negative electrode active material with the binder may be 8.0% or more, 10% or more, 12% or more, 14% or more, 16% or more, or 18% or more, and may be 25% or less, 23% or less, or 21% or less.

[0034] The coating of the negative electrode active material with a binder means that the binder is disposed (exists) on the surface of the negative electrode active material, and typically indicates that the binder is present in an attached or bonded state, and part of the binder may be contained even inside the negative electrode active material.

[0035] The coverage of the negative electrode active material by the binder can be determined by energy dispersive X-ray spectroscopy (EDX). Specifically, the side surface of the negative electrode active material layer is observed by a scanning electron microscope (SEM), and then elements contained only in the binder, for example, fluorine atoms when PVdF is used as the binder, are mapped by EDX. The areas of the binder and the negative electrode active material are calculated by binarizing the image data obtained by mapping. The coverage (%) of the negative electrode active material by the binder can be calculated as the ratio of the area of ​​the binder to the area of ​​the negative electrode active material.

[0036] "battery" The battery of the present disclosure includes the negative electrode active material layer of the present disclosure.

[0037] The battery of the present disclosure may be a liquid battery containing an electrolytic solution as an electrolyte layer, or may be a solid-state battery having a solid electrolyte layer as an electrolyte layer. In the present disclosure, a "solid-state battery" means a battery using at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. The battery of the present disclosure may also be an all-solid-state battery, i.e., a battery using only a solid electrolyte as an electrolyte.

[0038] (liquid battery) When the battery of the present disclosure is a liquid battery, it may further include a positive electrode active material layer and an electrolytic solution as an electrolyte layer, and may include a separator between the positive electrode active material layer and the negative electrode active material layer.

[0039] (Cathode active material layer) The positive electrode active material layer may contain, in addition to the positive electrode active material, a binder, a conductive assistant, and a solid electrolyte, if necessary.

[0040] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), lithium nickel-cobalt-manganese oxide (NCM), LiCO 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y M y Li-Mn spinel substituted with different elements having a composition represented by O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), LiNi x Co y Al z The oxygen saturation agent may be, but is not limited to, O2(NCA), etc.

[0041] For the binder, the conductive assistant, and the solid electrolyte, the above description of "<Configuration of the negative electrode active material layer>" can be referred to.

[0042] (Positive electrode current collector layer) The positive electrode active material layer may be formed on the positive electrode current collector layer. The material used for the positive electrode current collector layer is not particularly limited, but any material that can be used as a positive electrode current collector for a battery can be appropriately adopted. For example, it may be, but is not limited to, aluminum, stainless steel (SUS), chromium, gold, platinum, iron, titanium, zinc, etc., or these metals plated, coated, or vapor-deposited with nickel, chromium, carbon, etc.

[0043] (electrolyte) The electrolyte is not particularly limited, but preferably contains a supporting salt and a solvent.

[0044] Examples of supporting salts (lithium salts) for electrolytes having lithium ion conductivity include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6, and organic lithium salts such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, and LiC(CF3SO2)3.

[0045] The solvent used in the electrolyte is not particularly limited, but may be a non-aqueous solvent or an aqueous solvent.

[0046] Examples of non-aqueous solvents include cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), and chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). One type of electrolyte may be used alone, or two or more types may be used in combination. The electrolyte preferably contains two or more types of solvents.

[0047] Examples of the aqueous solvent include those containing water as a solvent, and may contain a solvent other than water in addition to water. Examples of the solvent other than water include one or more organic solvents selected from ethers, carbonates, nitriles, alcohols, ketones, amines, amides, sulfur compounds, and hydrocarbons.

[0048] (Separator) The separator is not particularly limited, but for example, a polyolefin-based, polyamide-based, polyimide-based, or other nonwoven fabric can be used.

[0049] (solid battery) In the case of a solid-state battery, the battery of the present disclosure may further include a positive electrode active material layer and a solid electrolyte layer as an electrolyte layer.

[0050] The positive electrode active material layer may contain, in addition to the positive electrode active material, a binder, a conductive assistant, a solid electrolyte, etc. as necessary. The description in "(Liquid Battery)" can be referred to.

[0051] The solid electrolyte layer may contain, in addition to the solid electrolyte, a binder, etc., as necessary. For the solid electrolyte and the binder, the above description regarding "<Configuration of the negative electrode active material layer>" can be referred to.

[0052] <<Method for producing negative electrode active material according to the present disclosure>> The negative electrode active material layer of the present disclosure can be produced by a method including the following steps: Mixing a carbon-based negative electrode active material and a binder in an amount of 4.0 to 9.0 mass% based on the total amount of the negative electrode active material layer to prepare a negative electrode mixture; and The negative electrode mixture is applied onto a substrate by a dry process to form the negative electrode active material layer.

[0053] According to the method for producing an anode active material layer of the present disclosure, it is possible to obtain an anode active material layer that contributes to improving the discharge capacity and resistance of a battery. Furthermore, according to the method for producing an anode active material layer of the present disclosure, an anode mixture in a powder state can be placed on a current collector to produce an anode active material layer. In other words, unlike the conventional method, a material that does not contain a solvent can be used, and therefore the step of removing the solvent can be omitted.

[0054] <Negative electrode mixture> The negative electrode mixture contains a carbon-based negative electrode active material and a binder, and may optionally contain a conductive additive, a solid electrolyte, and the like.

[0055] The negative electrode mixture may be in a dry state or in a wet state. That is, the negative electrode mixture may contain a solvent (liquid). However, the negative electrode mixture is different from the negative electrode mixture slurry (particle dispersion liquid). In the negative electrode mixture, the solvent forms droplets, and the solvent (liquid) is dispersed in the powder (solid). On the other hand, in the negative electrode mixture slurry, the solvent is the dispersion medium, and the powder (solid) is dispersed in the solvent (liquid).

[0056] For the carbon-based negative electrode active material and binder contained in the negative electrode mixture, the description in "<Constitution of the negative electrode active material layer>" can be referred to. For the binder content, the description in "<Binder content of the negative electrode active material layer>" can be referred to.

[0057] For details regarding the conductive assistant and solid electrolyte optionally contained in the negative electrode mixture, the description in "<Configuration of the negative electrode active material layer>" can be referred to.

[0058] The negative electrode mixture can be obtained by mixing a mixture containing a carbon-based negative electrode active material and a binder using, for example, a multipurpose small-sized mixer and grinder, but is not limited to this case.

[0059] (Dry method) The dry method is not particularly limited as long as it is a method for forming an electrode active material layer on a current collector using the negative electrode mixture. The dry method is not particularly limited, but examples thereof include electrostatic coating and rolling film formation.

[0060] An example of electrostatic coating is electrostatic screen film formation, but is not limited to this. Specifically, a high voltage is applied between an electrostatic screen and a current collector, and an electrostatic field is generated between the electrostatic screen and the current collector. When an electrically charged electrode mixture is dropped into the electrostatic field through an opening in the electrostatic screen, a Coulomb force is generated in the electrode mixture, which is attracted toward the current collector, which is the counter electrode, and the electrode active material layer is thereby formed. In addition, an example of roll film formation is lamination of a free-standing film of the electrode active material layer on the current collector, but is not limited to this.

[0061] (base material) The material used for the substrate is not particularly limited, but any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, copper, copper alloy, stainless steel (SUS), nickel, and these metals plated, coated, or vapor-deposited with nickel, chromium, carbon, etc. may be used, but are not limited to these. EXAMPLES

[0062] The present disclosure will be described in more detail with reference to the following examples, but the scope of the present disclosure is not limited to these examples.

[0063] Example 1 <Preparation of negative electrode active material layer A1> Graphite (particle size 20 μm) (95.0 parts by mass) as a negative electrode active material and polyvinylidene fluoride (PVdF) (particle size 150 nm) (5.0 parts by mass) as a binder were put into an MP mixer (multipurpose small mixer and grinder), and a composite treatment was performed for 2 minutes at a rotation speed of 10,000 rpm to obtain a negative electrode composite material. Next, the obtained negative electrode composite material was formed on a Cu foil (8 μm) as a negative electrode current collector by an electrostatic screen film formation method under the conditions of a voltage of 0.5 kV and a distance of 1 cm between the current collector foil and the screen. Thereafter, both sides of the negative electrode composite material formed on the Cu foil were sandwiched between flat plates heated at 160 ° C. and pressed with a load of 5 ton for 1 minute. Thereby, a negative electrode active material layer A1 in which the negative electrode composite material was fixed to the Cu foil was obtained.

[0064] <Coverage of negative electrode active material layer A1> The side surface of the negative electrode active material layer A1 was observed by SEM, and fluorine atoms contained only in the PVdF binder were mapped by EDX. The obtained image was then binarized to calculate the binder area. The binder coverage was calculated from the binder area relative to the particle area. The binder coverage of the negative electrode active material layer A1 was 10.1%.

[0065] <Preparation of Positive Electrode Active Material Layer B1> A positive electrode mixture slurry was prepared by mixing nickel-cobalt-manganese oxide (NCM) (particle size 3-10 μm) (97.5 parts by mass) as a positive electrode active material, acetylene black (1.5 parts by mass) as a conductive additive, PVdF (1.0 part by mass) as a binder, and an appropriate amount of NMP as a dispersion medium. The obtained positive electrode mixture slurry was applied to an Al foil (12 μm) as a positive electrode current collector and dried to prepare a positive electrode active material layer B1 on the positive electrode current collector.

[0066] <Preparation of battery C1> The negative electrode active material layer A1 and the positive electrode active material layer B1 were placed opposite each other with a separator interposed therebetween and housed in a container. Then, 1.14M LiPF6 / ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) (30: 34: 36 vol%) was poured into the container as an electrolyte, and the container was sealed to prepare a battery C1.

[0067] <Cell capacity of battery C1> Battery C1 was discharged under constant current and constant voltage conditions (current amount 0.3 C, voltage 4.25 V to 2.5 V, cut current 1 / 20 C) to calculate the discharge capacity. The discharge capacity of battery C1 was 190 mAh / g.

[0068] <Reaction resistance of battery C1> The SOC (State of Charge) of the battery C1 was adjusted to 50%. Next, the AC impedance of the battery C1 was measured, and the reaction resistance was calculated from the Cole-Cole plot. The reaction resistance of the battery C1 was 0.33 Ω.

[0069] Example 2 <Preparation of negative electrode active material layer A2> Except for using graphite (particle size 20 μm) (92.5 parts by mass) as the negative electrode active material and PVdF (particle size 150 nm) (7.5 parts by mass) as the binder, a negative electrode active material layer A2 fixed to a Cu foil was produced in the same manner as in Example 1. The binder coverage of the electrode active material layer A2 was 20.0%.

[0070] <Preparation of battery C2> Except for using the negative electrode active material layer A2 instead of the negative electrode active material layer A1, a battery C2 was produced in the same manner as in “Preparation of battery C1” in Example 1. The results of the cell capacity and reaction resistance of battery C2 are shown in Table 1 below.

[0071] Comparative Example 1 <Preparation of negative electrode active material layer a1> Except for using graphite (particle size 20 μm) (97.5 parts by mass) as the negative electrode active material and PVdF (particle size 150 nm) (2.5 parts by mass) as the binder, a negative electrode active material layer A2 fixed to a Cu foil was produced in the same manner as in “Preparation of negative electrode active material layer A1” in Example 1. The binder coverage of the electrode active material layer a1 was 4.0%.

[0072] <Creating battery c1> Except for using the negative electrode active material layer a1 instead of the negative electrode active material layer A1, a battery c1 was produced in the same manner as in “Preparation of Battery C1” in Example 1. The results of the cell capacity and reaction resistance of the battery c1 are shown in Table 1 below.

[0073] Comparative Example 2 <Preparation of negative electrode active material layer a2> A negative electrode active material layer A2 fixed to a Cu foil was produced in the same manner as in "Preparation of negative electrode active material layer A1" in Example 1, except that graphite (particle size 20 μm) (90.0 parts by mass) was used as the negative electrode active material and PVdF (particle size 150 nm) (10.0 parts by mass) was used as the binder. The binder coverage of the electrode active material layer a1 was 28.0%.

[0074] <Creating battery c2> Except for using the negative electrode active material layer a2 instead of the negative electrode active material layer A1, a battery c2 was produced in the same manner as in “Preparation of Battery C1” in Example 1. The results of the cell capacity and reaction resistance of the battery c2 are shown in Table 1 below.

[0075] [Table 1]

[0076] Batteries were fabricated using negative electrode active material layers with different binder amounts fabricated by a dry process and positive electrode active material layers prepared from positive electrode mixture slurries, and the discharge capacity and reaction resistance were evaluated.

[0077] Battery C1 including a negative electrode active material layer A1 with a binder content of 5.0% and battery C2 including a negative electrode active material layer A2 with a binder content of 7.5% were batteries with low reaction resistance and high discharge capacity (Examples 1 and 2).

[0078] However, the battery c1 including the negative electrode active material layer a1 with a binder amount of 2.5% had a low reaction resistance but a low discharge capacity (Comparative Example 1). When the binder amount was small and the coverage of the negative electrode active material by the binder was small, it is believed that SEI was formed on the graphite surface, increasing the irreversible capacity and thereby decreasing the discharge capacity.

[0079] In addition, the battery c2 including the negative electrode active material layer a2 with a binder content of 10.0% had a high discharge capacity but a high resistance (Comparative Example 2). When the binder content is large and the coverage of the negative electrode active material by the binder is high, it is considered that the binder inhibits the conduction of lithium ions, thereby increasing the reaction resistance.

[0080] Although preferred embodiments of the negative electrode active material layer, method of manufacturing the negative electrode active material layer, and battery of the present disclosure have been described, those skilled in the art will recognize that modifications are possible without departing from the scope of the claims.

Claims

1. A negative electrode active material layer for a battery, comprising: the negative electrode active material layer includes a carbon-based negative electrode active material and a binder coating the carbon-based negative electrode active material, The content of the binder is 4.0 to 9.0% by mass with respect to the total amount of the negative electrode active material layer, and The coverage of the negative electrode active material by the binder is 8.0 to 25%. A negative electrode active material layer for a battery.

2. 2. The negative electrode active material layer according to claim 1, wherein the content of the binder is 6.0 to 9.0 mass % with respect to the total amount of the negative electrode active material layer.

3. 2. The negative electrode active material layer according to claim 1, wherein the content of the binder is 7.0 to 8.0 mass % with respect to the total amount of the negative electrode active material layer.

4. The negative electrode active material layer according to claim 1 , wherein the binder is polyvinylidene fluoride.

5. A battery comprising the negative electrode active material layer according to any one of claims 1 to 4.

6. A method for producing a negative electrode active material layer according to any one of claims 1 to 4, comprising the steps of: Mixing a carbon-based negative electrode active material and a binder in an amount of 4.0 to 9.0 mass% based on the total amount of the negative electrode active material layer to prepare a negative electrode mixture; and The negative electrode mixture is applied onto a substrate by a dry process to form the negative electrode active material layer; The method for producing a negative electrode active material layer includes the steps of:

7. The method according to claim 6 , wherein the dry process is electrostatic coating.

8. The carbon-based negative electrode active material has an average particle size of 5 to 30 μm, and The method according to claim 6, wherein the average particle size of the binder is 100 nm to 500 nm.

Citation Information

Patent Citations

  • Positive electrode material for lithium secondary battery, and positive electrode and lithium secondary battery using the same

    JP2001135314A

  • Dry electrode for energy storage device and its manufacturing method

    JP2017517862A

  • Electrode manufacturing method and electrode manufacturing device

    JP2023016208A

  • Electrode for lithium ion battery and manufacturing method thereof

    JP2023082849A

  • Fluoropolymer Binder

    JP2024519717A